Real Time Water Quality Monitoring in lakes with IOT application - Madzalan, Nur Ezzati Assiqin; Misman, Dalila; Ili Najaa Aimi Mohd Nordin (Progress in Engineering Application and Technology, 2022)
Taking care of the water quality in lakes is crucial to keep the living things in them alive and well. It is an ecosystem that we need to maintain. A good water quality monitoring is one of the ways that we can do to maintain a healthy ecosystem for the lake. Thus, creating demands for a good monitoring system is making water quality control more efficient. During the completion of this project, there are various articles and projects that explains about the water quality for lake protection, and they were able to drastically change their method to become more reliable and efficient to compete with today’s market. This project discusses the development of water quality control in lakes through its electronic and mechanical design. This project also uses an Arduino microcontroller to design a Real Time Water Quality in Lakes with IOT Application. The IOT application that is applied in the project will make monitoring the water quality easier by making it remotely display the water condition. Future researchers can improve the design and making it more neatly.